PENGEMBANGAN BUDIDAYA UDANG DAN POTENSI PENCEMARANNYA PADA PERAIRAN PESISIR - Yudhi Soetrisno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Becouse of the shrimp price in international market was high, Indonesia which have a big potential swamp for develop shrimp pond (tambak) plan to increase the shrimp production. Lately, intensive shrimp culture always failed due to decomposition of organic waste in the bottom created oxygen depletion and produced gases (NH3 and H2S) which dangerous to water organisms.To avoid the fenomema farmer threw out the organic waste to coastal water which can develop euthrofication, blooming and water quality degradation. This paper conclude that increasing of the shrimp production using intensive culture will create many problem, due to the existing technology was not completed by technology which can eliminate the organic waste in the pond. This paper suggest that before the intensive technology was completed with “waste water treatment” or “biomanipulation technology” which can eliminate the organic waste in the pond, the increasing of shrimp production will better using extensive program with conventional or semiintensive technology. Without all it the negative impact of organic waste in coastal waters will bigger than positive impact of increasing the shrimp production.